The United Nations in international history - Sayward, Amy L. 1969- (London New York Bloomsbury Academic, 2017)
"Examines how the United Nations has developed as an international arena for diplomacy"--Provided by publisher.
Machine generated contents note: -- List of Figures -- Series Editor's Preface -- Preface and Acknowledgments -- Foreword -- List of Abbreviations -- 1. Introduction: An Invitation -- 2. The National and International Origins of the United Nations -- 3. The Cold War Borderland -- 4. Preventing War and Promoting Peace through Social and Economic Programs -- 5. The Development Enterprise -- 6. Making and Keeping the Peace: U.N. Peace-Keeping and Refugee Assistance Operations -- 7. The Middle East and the United Nations -- 8. Defining Human Rights, International Justice, and Genocide -- 9. Conclusion: Join the Conversation! -- Notes -- Index.
Includes bibliographical references and index.
Keywords: United Nations -- History; Diplomacy